El desarrollo de la conciencia ambiental en la didáctica del sistema educativo - Rodriguez La Rosa, Sara Nataly (2024)
This study aims to present the different theories on the development of environmental consciousness that, throughout history, have influenced educational system didactics and human behavior, in order to achieve a sustainable pro-ecological attitude change. To do this, the PRISMA methodology was used and 10 articles were prioritized, respecting eligibility criteria and filters. The inquiry was conducted considering variables according to data from Web of Science and Scopus for the period 2020-2023. The results suggest that the various theories on the development of environmental consciousness embraced by the Peruvian educational system have significantly impacted didactics focused on the holistic formation of the individual in favor of the environment; an aspect that gives us hope for creating a world where there is a balance between humans and the environment, with emphasis on sustainability and respect for all elements and living beings, where ecological morality and ethics prevail over any profit-seeking endeavors.